Study Guide for Statistics for Business and Financial Economics: A Supplement to the Textbook by Cheng-Few Lee, John C. Lee and Alice C. Lee - Moy, Ronald L (Springer, 2015)
This Study Guide accompanies Statistics for Business and Financial Economics, 3rd Ed. (Springer, 2013), which is the most definitive Business Statistics book to use Finance, Economics, and Accounting data throughout the entire book. The Study Guide contains unique chapter reviews for each chapter in the textbook, formulas, examples and additional exercises to enhance topics and their application. Solutions are included so students can evaluate their own understanding of the material. With more real-life data sets than the other books on the market, this study guide and the textbook that it accompanies, give readers all the tools they need to learn material in class and on their own. It is immediately applicable to facing uncertainty and the science of good decision making in financial analysis, econometrics, auditing, production and operations, and marketing research. Data that is analyzed may be collected by companies in the course of their business or by governmental agencies. Students in business degree programs will find this material particularly useful to their other courses and future work.